Lei da ficha limpa: causas de inelegibilidade e princípio da presunção de inocência - Santos, Gesiane Pereira dos (2013)
To analyze the supposed violation of the innocence presumption by ineligibility causes due to non definitive condemnations instituted by the Complimentary Law nº135 from 2010, nicknamed Law Clean Sheet. For this, provides theoretical base to the comprehension of these ineligibilities, weaving brief comments about democracy, suffrage, political rights and eligibility. In a posterior moment, executes a prior examination about normativity and juridicity of the principles as a whole, passing through the analysis of the innocence presumption principle. Lastly, dedicates lines to the presentation of the jurisprudential understanding of the Supreme Federal Court about the subject, with a prior study on the Complimentary Law nº 135/2010, Law Clean Sheet's history. Concludes that the Law Clean Sheet doesn't violates the innocence presumption principle.